2006
DOI: 10.1261/rna.2339606
|View full text |Cite
|
Sign up to set email alerts
|

Multiple domains of EBER 1, an Epstein-Barr virus noncoding RNA, recruit human ribosomal protein L22

Abstract: EBER 1, asmall noncoding viral RNA abundantly expressed in all cells transformed by Epstein-Barr virus (EBV), has been shown to associate with the human ribosomal protein L22. Here we present in vitro binding studies using purified RNAs and recombinant proteins. Electrophoretic mobility-shift assays (EMSAs) show that recombinant L22 (rL22) and maltose-binding protein (MBP)-tagged L22 protein bind EBER 1i nv itro, both forming three specific protein-dependent mobility shifts. Use of am ixture of rL22 and MBP-L2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
75
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(75 citation statements)
references
References 46 publications
0
75
0
Order By: Relevance
“…Surprisingly, although EBER1 could be selected by an antisense oligonucleotide, La and L22, the best-characterized EBER1 interacting partners, were not coselected. The region of EBER1 we identified as a target for hybridization and RNase H cleavage overlaps with stemloop III, previously characterized as the major binding site for L22 (Toczyski and Steitz 1993;Fok et al 2006b). Whereas in prior immunoprecipitation experiments >95% of total EBER1 was precipitated by anti-L22 antibodies (Toczyski and Steitz 1993), oligonucleotide selection captured only 5% (Fig.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Surprisingly, although EBER1 could be selected by an antisense oligonucleotide, La and L22, the best-characterized EBER1 interacting partners, were not coselected. The region of EBER1 we identified as a target for hybridization and RNase H cleavage overlaps with stemloop III, previously characterized as the major binding site for L22 (Toczyski and Steitz 1993;Fok et al 2006b). Whereas in prior immunoprecipitation experiments >95% of total EBER1 was precipitated by anti-L22 antibodies (Toczyski and Steitz 1993), oligonucleotide selection captured only 5% (Fig.…”
Section: Discussionmentioning
confidence: 88%
“…This behavior is reminiscent of RNP complex formation between EBER1 and L22, in which multiple stem-loops within EBER1 contribute to the RNA-protein interaction (Fok et al 2006b). AUF1 and L22, however, form distinctly different RNP complexes with EBER1, since single stem-loop deletions did not result in a decrease in the overall number of AUF1-EBER1 RNP complexes (data not shown), in contrast to L22 (Fok et al 2006b). EBER1 and the TNFa-ARE formed RNP complexes at comparable AUF1 concentrations (Fig.…”
Section: Eber1 Can Compete With the Binding Of Auf1 To Are Rna In Vitromentioning
confidence: 99%
See 1 more Smart Citation
“…There is no published evidence to support a role for most genes in the region (Table 1) as TSGs in cancer generally, or neuroblastomas in particular. RPL22 recruits the EpsteinBarr early RNA and is linked to lymphoma associated with Epstein-Barr virus (Elia et al, 2004;Fok et al, 2006). ICMT is an isoprenylcysteine methyltransferase that has been implicated in carcinogenesis and as a target for anticancer therapy (Bergo et al, 2004;WinterVann et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Previous in vitro binding studies suggested that EBER1 stem-loops III and IV serve as binding sites for L22 (Toczyski and Steitz 1993;Dobbelstein and Shenk 1995). Recently, we carried out experiments using recombinant L22 protein in electrophoretic mobility-shift assays and found that the EBER1 molecule harbors three L22-binding sites (Fok et al 2006b). These are the above- Some gammaherpesviruses encode nuclear noncoding RNAs (ncRNAs) that assemble with host proteins.…”
Section: Epstein-barr Virus (Ebv) Infection Of Human B Lymphocytes Ofmentioning
confidence: 99%